Pengaruh Pendapatan Biaya Serta Efesiensi Beban Operasional Dalam Mengukur Kinerja Keuangan Perusahaan: Studi Kasus Pada Cv. Intiga Harapan Sukses - Periyadi Periyadi; Noorlalily Maulida; Idzani Muttaqin (Pusat Riset dan Inovasi Nasional, 2025)
Every company aims to achieve the greatest possible profit by considering the value of the benefits of its business activities. Profitability, which reflects the company's ability to generate revenue and profit, is one of the main aspects in evaluating the company's performance. Management, as the company's operational implementer, is responsible for the continuity of the operation. Management not only focuses on profit but also on how their business activities provide value to various stakeholders, as this can have a positive impact on the company's reputation and long-term sustainability. The results of the study show that the revenue aspect shows positive results. This revenue growth is influenced by successful market expansion, product diversification that attracts more consumers, and digital marketing strategies that increase brand visibility and customer engagement. The company's financial performance based on the cost aspect shows efficient management. Despite an increase in total operating costs, the cost-to-income ratio shows a stable trend, indicating that the company has succeeded in controlling costs without sacrificing efficiency and based on the profitability aspect shows a significant increase in gross profit and net profit. This increase in profitability reflects efficiency in managing operating costs and effective taxation strategies.